The Effect of Generational Differences on Performance Employees at PLN UP2D Makassar - Awaluddin Jabbar; Dg. Makkalassa; Sri Andayaningsih (Journal Social Society, 2026)
The urgency of this study is to examine how generational differences influence employee performance at PLN UP2D Makassar, enabling the organization to develop more effective workforce management strategies in a multigenerational workplace. Rapid technological change and the increasing presence of multigenerational employees in the workplace have created challenges for organizations in managing differences in work values, communication styles, and technological adaptability. Therefore, understanding the impact of generational differences on employee performance has become increasingly important for organizations seeking to maintain productivity and competitiveness. This study aims to examine and analyze the effect of generational differences on employee performance at PLN UP2D Makassar. The research employed a quantitative approach using a causal-comparative design. Data were collected through questionnaires distributed to all employees, totaling 70 respondents, using a saturated sampling technique. Data analysis was conducted using simple linear regression supported by validity, reliability, and classical assumption tests with SPSS. The findings reveal that generational differences have a positive and significant effect on employee performance. This is evidenced by a regression coefficient of 0.960 and a significance value of 0.000, which is below the 0.05 threshold. Additionally, the t-statistic value of 14.957 indicates a strong influence of generational differences on performance. The coefficient of determination (R²) of 0.767 suggests that 76.7% of the variation in employee performance can be explained by generational differences, while the remaining 23.3% is influenced by other variables not included in the model. The results imply that organizations should implement inclusive human resource management strategies that accommodate multigenerational characteristics through adaptive communication, collaborative work systems, and technology-based training programs. In conclusion, effective management of generational diversity can improve employee performance, strengthen workplace collaboration, and enhance organizational productivity.